2023
DOI: 10.3390/biomedicines11030684
|View full text |Cite
|
Sign up to set email alerts
|

Facial Skin Microbiome: Aging-Related Changes and Exploratory Functional Associations with Host Genetic Factors, a Pilot Study

Abstract: In this exploratory study, we investigate the variation in the facial skin microbiome architecture through aging and their functional association with host genetic factors in a cohort of healthy women, living in the same area and without cutaneous diseases. Notably, facial skin microbiota (SM) samples were collected from a cohort of 15 healthy Caucasian females, firstly divided into three age groups (younger women aged 20–35 years old; middle aged women of 36–52 years old; and older women aged 53–68 years old)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Changes in skin microbiome diversity and composition at different taxonomic levels linked to ageing were described previously in several female cohort studies. However, mean age differences between examined old and young age groups in these studies were between 32 and 39 years ( Shibagaki et al, 2017 ; Somboonna et al, 2017 ; Jugé et al, 2018 ; Kim et al, 2019 ; Kim et al, 2022 ; Zhou et al, 2023 ), or examined age groups were multimodal distributed ( Howard et al, 2022 ; Russo et al, 2023 ). Ageing is a complex and multifactorial process, and the composition of the skin microflora can be influenced by age-dependent exposure time spans to environmental stressors and intrinsic factors ( Khmaladze et al, 2020 ), such as solar UV irradiation, particulate matter, cosmetic products, climate, nutritional ingredients, as well as individual genetic background, gender, menopause-associated hormonal changes and immune-senescence ( Cisneros et al, 2022 ).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Changes in skin microbiome diversity and composition at different taxonomic levels linked to ageing were described previously in several female cohort studies. However, mean age differences between examined old and young age groups in these studies were between 32 and 39 years ( Shibagaki et al, 2017 ; Somboonna et al, 2017 ; Jugé et al, 2018 ; Kim et al, 2019 ; Kim et al, 2022 ; Zhou et al, 2023 ), or examined age groups were multimodal distributed ( Howard et al, 2022 ; Russo et al, 2023 ). Ageing is a complex and multifactorial process, and the composition of the skin microflora can be influenced by age-dependent exposure time spans to environmental stressors and intrinsic factors ( Khmaladze et al, 2020 ), such as solar UV irradiation, particulate matter, cosmetic products, climate, nutritional ingredients, as well as individual genetic background, gender, menopause-associated hormonal changes and immune-senescence ( Cisneros et al, 2022 ).…”
Section: Introductionmentioning
confidence: 72%
“…These findings are interesting, even though a confirmation with higher subject number is required, in that inclusion of volunteers with irregular menstrual periods inaccurately in either pre- or postmenopausal groups may significantly impact respective microbial diversity calculations. Inappropriate inclusion of transmenopausal subjects in postmenopausal groups, as well as other confounding age-dependent and extrinsic factors may explain, why a minority of previous studies detected a trend towards higher bacterial diversity on face of younger volunteers ( Kim et al, 2019 ; Russo et al, 2023 ). Lastly, given that the average age of volunteers in our peri/menopausal group (45.8 ± 4 years) was similar to the directly compared premenopausal group (48.1 ± 3 years), further supports our hypothesis that the impact of menopausal-driven hormonal changes on facial microbiome composition may be more significant than age-dependent skin physiological adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of matrix metalloproteinases (MMPs), which are induced by reactive oxygen species (ROS), leads to the degradation of the ECM. 39,40 As collagen degrades, wrinkles deepen and skin elasticity decreases. 41 Additionally, it has been clarified that green coffee oil (GCO) stimulates human skin fibroblasts to synthesize ECM compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Si et al (2015) on the skin microbiota diversity of monozygotic and dizygotic twins suggested that variation is due to host genetics, age, and skin pigmentations (Si et al, 2015). A recent study on facial skin microbiota investigated genetic factors that influence aging-related pathways causing skin microbial differences in healthy Italian women in three age groups (younger, middle-aged, and older) (Russo et al, 2023). However, an in-depth analysis of heritability of a skin microbiota across generations will require larger number of families and samples per generation.…”
Section: Discussionmentioning
confidence: 99%